2017
DOI: 10.1097/aog.0000000000001982
|View full text |Cite
|
Sign up to set email alerts
|

State Medicaid Coverage of Medically Necessary Abortions and Severe Maternal Morbidity and Maternal Mortality

Abstract: Objective To estimate the association between state Medicaid coverage of medically necessary abortion and severe maternal morbidity and in-hospital maternal mortality in the U.S. Methods We used data on pregnancy-related hospitalizations from the Nationwide Inpatient Sample from 2000 to 2011 (weighted n=38,016,845). State-level Medicaid coverage of medically necessary abortion for each year was determined from Guttmacher Institute reports. We used multivariable logistic regression to examine the association … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 17 publications
1
11
0
Order By: Relevance
“…Since 2009, researchers have continued to study impacts of restricted Medicaid funding for abortion. Methodologically sophisticated studies have documented Medicaid funding restrictions’ impact on maternal morbidity and infant mortality [10, 11]. Other research examined women’s and provider’s experiences with Medicaid coverage and found that, even when Medicaid can pay for abortion, it sometimes does not, leading to delays and financial and emotional impacts on women obtaining abortions [8, 12–15].…”
Section: Introductionmentioning
confidence: 99%
“…Since 2009, researchers have continued to study impacts of restricted Medicaid funding for abortion. Methodologically sophisticated studies have documented Medicaid funding restrictions’ impact on maternal morbidity and infant mortality [10, 11]. Other research examined women’s and provider’s experiences with Medicaid coverage and found that, even when Medicaid can pay for abortion, it sometimes does not, leading to delays and financial and emotional impacts on women obtaining abortions [8, 12–15].…”
Section: Introductionmentioning
confidence: 99%
“…Responding to women’s needs around abortion includes expanding access to health insurance that includes abortion coverage. In the United States, state Medicaid coverage of medically necessary abortion reduced the risk of severe maternal morbidity by an average of 16% [ 101 ].…”
Section: Resultsmentioning
confidence: 99%
“…In Sub-Saharan Africa, transitioning from unsafe to safe abortion is estimated to result in 18,300 (Nigeria) and 29,000 (Ghana) years of life gained per 100,000 safe abortion procedures. And in the United States, societal benefits from increasing access to abortion services through state Medicaid coverage for medically-necessary abortion services is associated with fewer cases of severe maternal morbidity compared to states without such coverage [95].…”
Section: Macroeconomics Benefits and Valuementioning
confidence: 99%